How should "hot" players in basketball be defended? The use of fast-and-frugal heuristics by basketball coaches and players in response to streakiness - Csapo, P.; Avugos, S.; Raab, M.; Bar-Eli, M. (Journal of Sports Sciences, 2015)
Previous research has shown that changes in shot difficulty may have rendered the hot-hand effect in basketball unobservable and are potentially a result of defensive adjustments. However, it has not been directly analysed whether strategic changes indeed take place in response to streakiness and whether they are effective with respect to winning games. The current work consists of an experimental study with 18 professional coaches and 20 players based on video sequences from National Basketball Association games, where the shown player displayed a streaky performance in half of the sequences. While coaches were asked to devise a defensive strategy after each viewed sequence, players had to assume the role of the shown player and decide whether to shoot or pass the ball. We find that coaches tended to increase the defensive pressure significantly more often on presumably hot players and thus make use of the hot-hand heuristic. Meanwhile, players chose to shoot more frequently in low-pressure and streaky situations but selected "pass" regardless of the previous performance when they faced increased defensive pressure. Assuming that a streaky player`s performance is indeed elevated during hot phases, hot-hand behaviour can be considered adaptive in certain situations as it led hot players to pass instead of shoot.